LEGAL PAPERS AND THE PRACTICE OF PROTECTING THE INTERNATIONAL PEACE MISSION PERSONNEL IN INDONESIA - Iqbal, Muhammad Putra (UI Scholars Hub, 2015)
The Helsinki Memorandum of Understanding (MoU) signed in 2005 and facilitated by Finland former President Martii Ahtisaari with support from the European Union has brought peace to Aceh after 30 years armed conflict between the Government of Indonesia and the Free Aceh Movement. The EU involves both in short and long term monitoring programs. During the mission in Aceh, several serious incidents involving the use of light weapons and directed toward the EU peace mission were recorded. Indonesian domestic law acknowledges the protection must be delivered to the internationally protected person based on Vienna Convention 1961 on Diplomatic Protection and other related conventions. Would the ratification of Vienna Convention satisfy the protection for the EU peace mission? An Act on Foreign Relation enacted as legal basis for international relation including with the EU and its missions argue would be able to answer the question. On the other side, EU enacted Protocol on the Privileges and Immunities of the European Union (the Protocol) to secure its mission overseas. The protocol is a specific legal instrument within the EU legal regime that was enacted to fulfill the needs of an international legal instrument on EU’s legal personality particularly the privileges and immunities aspects. The Protocol answers a main concern on legal relation between a State and EU mission including EU peace missions. However, as a non-member State and as a matter of law, Indonesia does not ratify the Protocol consequently Indonesia does not bind with the Protocol. The Indonesia Act on Foreign Relation is considered very basic for the current condition. Consequently, different interpretation between related State organs occurred. As a result, ineffective protection for the protected person such mandated by the international law remain measured. This condition does not suppose to happen since although remain debatable, an international cooperation, an influential external power nowadays is playing very important role including in a peace process. Moreover, as Indonesia is strengthening its position within the international community, some improvements crucial to be supported.